Therapeutic notepad for couples – The path to shared happiness - Santos, Isabel dos; Saraiva, Beatriz; Coelho, Marta; Salvador, Olivia; Mesquita, Edgar Martins (Seven Editora, 2024)
Human beings have an inherent need and desire to build relationships and, when these relationships are healthy, they can lead to better mental health and emotional well-being. A satisfactory marital relationship brings a number of benefits to the individual, such as life satisfaction and emotional health. Research suggests that social support and the emotional impact of a committed relationship can be a buffer against stress, which can contribute to happiness. The present study aims to understand the usefulness and practicability of a therapeutic notepad for married couples, composed by inspirational quotes and tasks, underlying happiness and well-being, elaborated and materialized by the first author in the course of her 30 years of clinical practice. A total of 60 couples participated in this study, with a total of 120 individuals, aged between 28 and 64 years (M=43.34; SD=12.43), equally distributed by sex. Firstly, a sociodemographic questionnaire was applied to collect personal data, then the Marital Scale (EMS) ENRICH (assessment and nurturing of relationship, communication and happiness issues) was administered, which translates into a fifteen-item instrument: ten of the items on the scale survey concern marital quality domains, while the other items compose a scale of marital conventionalization to correct the tendency to endorse unrealistically positive descriptions of marriage. Finally, a semi-structured interview was conducted to understand the functionality of the therapeutic notepad for couples. The results showed, both qualitatively and quantitatively, that the agenda can be assumed as a resource that promotes the happiness and well-being of a couple, as well as the reduction of the negative mood of both each individual and each other. This study focuses on the importance of well-being and happiness in the daily life of a marital relationship. This is an important contribution, as it allows us to assess that the therapeutic notebook for couples can lead to positive and encouraging results when applied. DOI:https://doi.org/10.56238/sevened2023.007-077